The mediation role of interest rate between financial liberalisation and financial stability - Muhamad Arifin, Nur Afizah; Mohd Ariffin, Noraini; Ramly, Zulkufly; Mohd Hashim, Maryam Jameelah (Universal Publishers, 2021)
As a financial intermediary, the banking industry is critical in mobilising funds between surplus and deficit firms. The global financial market has changed dramatically as a result of the transition from financial repression to financial liberalisation, which has resulted in increased cross-border capital flows and financial sector expansion. Liberalisation of the banking industry has pushed commercial banks to take on more risk, which may have a detrimental effect on financial stability and the survival of smaller banks. As a result, the purpose of this study was to examine the function of interest rates as a mediating factor in the link between financial liberalisation and financial stability in Malaysian conventional and Islamic banks. Due to Shariah constraints, Islamic banks' mediating effects may differ from those of conventional banks. PLS-SEM analysis of the research model found that interest rates strongly mediated the association between financial liberalisation and financial stability. Islamic banks, on the other hand, must preserve their stability through interest rate mediation in the context of financial liberalisation